The effect of prostate motion during hypofractionated radiotherapy can be reduced by using flattening filter free beams - Benedek, Hunor (Phys Imaging Radiat Oncol, 2018)
BACKGROUND AND PURPOSE: Hypofractionated radiotherapy of prostate cancer reduces the overall treatment time but increases the per-fraction beam-on time due to the higher fraction doses. This increased fraction treatment time results in a larger uncertainty of the prostate position. The purpose of this study was to investigate the effect of prostate motion during flattening filter free (FFF) Volumetric Modulated Arc Therapy (VMAT) in ultrahypofractionation of prostate cancer radiotherapy with preserved plan quality compared to conventional flattened beams. MATERIALS AND METHODS: Nine prostate patients from the Scandinavian HYPO-RT-PC trial were re-planned using VMAT technique with both conventional and flattening filter free beams. Two fractionation schedules were used, one hypofractionated (42.7 Gy in 7 fractions), and one conventional (78.0 Gy in 39 fractions). Pre-treatment verification measurements were performed on all plans and the treatment time was recorded. Measurements with simulated prostate motion were performed for the plans with the longest treatment times. RESULTS: All the 10FFF plans fulfilled the clinical gamma pass rate, 90% (3%, 2 mm), during all simulated prostate motion trajectories. The 10MV plans only fulfilled the clinical pass rate for three of the trajectories. The mean beam-on-time for the hypofractionated plans were reduced from 2.3 min to 1.0 min when using 10FFF compared to 10MV. No clinically relevant differences in dose distribution were identified when comparing the plans with different beam qualities. CONCLUSION: Flattening-filter free VMAT reduces treatment times, limiting the dosimetric effect of organ motion for ultrahypofractionated prostate cancer with preserved plan quality.